Phosphatase Shp2 regulates biogenesis of small extracellular vesicles by dephosphorylating Syntenin. Issue 4 (10th March 2021) - Zhang, Yuefei; Li, Yiqing; Liu, Pan; Gong, Dacheng; Zhou, Hui; Li, Wenjuan; Zhang, Huilun; Zheng, Wenfang; Xu, Jiaqi; Cheng, Hongqiang; Zhang, Xue; Ke, Yuehai
Abstract: As novel mediators of cell‐to‐cell signalling, small extracellular vesicles (sEVs) play a critical role in physiological and pathophysiological processes. To date, the molecular mechanisms that support sEV generation are incompletely understood. Many kinases are reported for their roles in sEV generation or composition, whereas the involvement of phosphatases remains largely unexplored. Here we reveal that pharmacological inhibition and shRNA‐mediated down‐regulation of tyrosine phosphatase Shp2 significantly increases the formation of sEVs. By Co‐immunoprecipitation (Co‐IP) and in vitro dephosphorylation assays, we identified that Shp2 negatively controlled sEV biogenesis by directly dephosphorylating tyrosine 46 of Syntenin, which has been reported as a molecular switch in sEV biogenesis. More importantly, Shp2 dysfunction led to enhanced epithelial sEV generation in vitro and in vivo. The increase of epithelial sEVs caused by shRNA‐mediated down‐regulation of Shp2 promoted macrophage activation, resulting in strengthened inflammation. Our findings highlight the role of Shp2 in regulating sEV‐mediated epithelial‐macrophage crosstalk by controlling sEV biogenesis through dephosphorylation of Syntenin Y46. The present study determines the strengthened inflammatory characteristics of alveolar macrophages elicited by epithelial sEVs transferred intercellularly. These findings provide a basis for understanding the mechanism of sEV formation and relevant function in epithelial‐macrophage crosstalk.